Current Issues of State and Private Ownership - Gabrielyan, Varduհi (Bulletin of Yerevan University G: Economics, 2016)
The effect of large-scale government intervention in the economy, being positive in the phase of the crisis, becomes negative in the phase of stable long-term economic growth. The trend towards denationalization of property was particularly apparent in the 1970- 1980's. In the shorter run, the relationship between the private and public sectors of the economy is also influenced by peculiarities of the business cycle development. During the global economic crisis of 2008-2009, many countries implemented anti-crisis measures of nationalization. In the 2010-2014, many governments have returned to programs of size limitation of the state sector and are developing projects of further privatization of companies to significantly improve the efficiency of their operations.
Keywords: state-owned enterprise, private company, nationalization, privatization, property, financial and real assets, efficiency